The Impact of COVID-19 Through the Lens of Islamic Law: An Indonesian Case - Mohammad Syahrul RA; Yusuf Hamdika; Sholahuddin Al-Fatih (University of Jember, 2020)
Coronavirus Disease 2019 (COVID-19), a virus found in China, has spread worldwide as it has become pandemic. As a result, significant and detrimental impacts are undeniable to global citizens, including those in Indonesia. With the government's suggestions like introducing physical distancing and large-scale social restriction, they slow down economic growth. Also, they impact religious practices, particularly those performed by Muslims in Indonesia. This paper will discuss the impact of the COVID-19 pandemic through the lens of Islamic law. There are two main issues to analyze. First, what is the impact of COVID-19 on community activities in the view of Islamic law? Second, what is the impact of COVID-19 on religious communities in carrying out worship? This paper finds that the COVID-19 pandemic has adversely impacted religious worship activities in public places by considering this virus's rapid transmission. It is followed by the closure of worship places to encourage citizens to practice their religious activities at home. Thus, the whole community was urged, and some were prohibited following the mapping zone experienced by each region. Given Islamic law is believed and trusted by Muslims, in the end, the government has issued a new normal policy by opening places of worship with health protocols. KEYWORDS: COVID-19, Islamic Law, Religious Practices, Indonesian Muslims.